1999
DOI: 10.1191/026921599676188597
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Assessment Measure (FIM + FAM) as part of the hospital discharge summary after brain injury rehabilitation

Abstract: The incorporation of FIM + FAM data in discharge summaries is worthwhile but the utility of this practice is still to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Research has suggested that 82% to 92% of general practitioners find the FIM+FAM scores to be useful as part of acute rehabilitation discharge reporting. 12 A literature search using MEDLINE revealed no studies examining the FIM+FAM in the TBI comprehensive day program setting. Despite good to excellent levels of reliability and evidence of construct validity, other factors must be considered to evaluate the utility of the FIM+FAM instrument in a TBI day program setting.…”
mentioning
confidence: 99%
“…Research has suggested that 82% to 92% of general practitioners find the FIM+FAM scores to be useful as part of acute rehabilitation discharge reporting. 12 A literature search using MEDLINE revealed no studies examining the FIM+FAM in the TBI comprehensive day program setting. Despite good to excellent levels of reliability and evidence of construct validity, other factors must be considered to evaluate the utility of the FIM+FAM instrument in a TBI day program setting.…”
mentioning
confidence: 99%
“…It is highly desirable to identify those patients who are likely to improve the most, to judge the success of treatment, to allow the family to adjust to the residual deficits and to plan services for survivors. There are a number of studies that have concentrated on predicting outcome soon after admission to acute hospital or soon after intensive care (Shah et al 1989, Giacino et al 1991, Pentland et al 1999. However, very few studies have addressed the outcome, based on function, in the later stages of recovery across rehabilitation.…”
Section: The Utility Of the Modified Barthel Index For Traumatic Braimentioning
confidence: 99%
“…The ability to care for self and to move to a self-sufficient status would add greatly to the independence of people with TBI. This self-sufficiency would allow them to explore further their ability to interact with their environment, such as in instrumental activities of daily living, and with other domains of quality of life assessments, such as employment opportunities (Gurka et al 1999, Pentland et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…It comprises 30 items (16 motor and 14 cognitive), which are each scored using a 7-point ordinal scale, rating performance from 1 ¼ 'total dependence' to 7 ¼ 'total independence'. It has been shown to have utility as an outcome measure for inpatient [6], community-based [7] and comprehensive day rehabilitation programmes [8] -providing both useful qualitative information [9] and a valid measure of outcome [8,10]. However, although it provides a reasonable assessment of physical and psychosocial disability for brain injured individuals, the published version of the UK FIMþFAM does not include basic practical household tasks or 'extended activities of daily living' (EADL) that are essential to independent living in the community.…”
Section: Introductionmentioning
confidence: 99%